Simulation modeling of student enrolment to solve operations problems: A case of the Saad Al- Abdullah Academy in Kuwait - Rashed M.F. Al-Therwah; Mahmoud Heshmat; Mahmoud El-Sharief; Ibrahim Mohamed Hassab -Allah (Alexandria Engineering Journal)
Educational institutions strive to achieve their goals efficiently and effectively by enhancing and continually developing their performance. This paper serves as a valuable resource for the management of academic institutions, highlighting key contemporary approaches in their management. It focuses on a case study of the new student registration procedure at Kuwait's Saad Al-Abdullah Academy for Security Sciences. The paper represents and replicates each stage of the student enrollment procedure. Data was gathered from 2024 applicants and reviewed by health personnel. The simulation results were examined to help enhance the system. Alternative models were created to address concerns highlighted in the original model. The first alternative model proposes executing the registration procedure digitally rather than manually. The second alternative model recommends increasing the workforce for each process. The study concluded that using ARENA software would significantly enhance the efficiency of the Academy's real enrollment system. The first alternative model increases the number of candidates who can complete their medical test in a day by 37 % compared to the initial model. The second alternative model improves system efficiency by 48 % with an increased workforce.